2019
DOI: 10.1038/s41598-019-46688-6
|View full text |Cite
|
Sign up to set email alerts
|

Establishing next-generation pest control services in rice fields: eco-agriculture

Abstract: Pesticides are commonly used in food crop production systems to control crop pests and diseases and ensure maximum yield with high market value. However, the accumulation of these chemical inputs in crop fields increases risks to biodiversity and human health. In addition, people are increasingly seeking foods in which pesticide residues are low or absent and that have been produced in a sustainable fashion. More than half of the world’s human population is dependent on rice as a staple food and chemical pesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 38 publications
1
54
0
6
Order By: Relevance
“…There is an increasing need to monitor arthropods in food plants and storage [3]. One of the most critical applications of insect monitoring is in the field of integrated pest management (IPM), which aims to optimize plant protection actions on arable fields and orchards [4,5]. It is essential in plant protection to ascertain the population size and activity time of different arthropod species.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing need to monitor arthropods in food plants and storage [3]. One of the most critical applications of insect monitoring is in the field of integrated pest management (IPM), which aims to optimize plant protection actions on arable fields and orchards [4,5]. It is essential in plant protection to ascertain the population size and activity time of different arthropod species.…”
Section: Introductionmentioning
confidence: 99%
“…Realization of the negative effects of fertilizers and pesticides, and the role of enemy-free space in initiating outbreaks of rice pests, has recently placed biodiversity management at the forefront of public research into rice crop protection. Over the last decade, research institutes in several Asian countries have initiated and/or completed projects aimed at enhancing regulation services provided by the natural enemies of rice pests, particularly planthopper and stemborer pests (e.g., China, Thailand and Vietnam [14]; the Philippines: [5]; Indonesia [15], India: [16]; and Bangladesh: [17]). The results from many of these projects have been generally positive.…”
Section: Introductionmentioning
confidence: 99%
“…For example, comparative studies have indicated that planting rice levees (known as bunds) with strips or patches of nectar-producing flowers increases natural enemy abundance and/or reduces pest incidence [14,16,17,18,19]. This can lead to a reduction in insecticide applications [14,20] and increased rice yields [14,17]. Planting vegetables on bunds also provides a supplementary income for rice farmers and promotes diet diversification of the farming household [18,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations